ChemInform Abstract: "On Water", Phosphine‐Free Palladium‐Catalyzed Room Temperature C—H Arylation of Indoles. Issue 12 (25th March 2014) - Islam, Saidul; Larrosa, Igor
Abstract The use of silver cyclohexanoate as base is crucial for the success of the title arylation reaction.